Catalytic Hydrothermal Liquefaction of Sugarcane Bagasse: Effect of Crystallization Time of Fe-MCM-41 and Process Parameters - Gopalakrishnan Govindasamy; Rohit Sharma; Sunu Subramanian (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Sugarcane is both food and energy crop providing sugar and energy products. Hydrothermal liquefaction (HTL) is gaining importance for the conversion of sugarcane bagasse to bio-oil, whose yield depends on the deoxygenation activity of the catalyst employed and process parameters. In this study, mesoporous Fe-MCM-41 catalysts were synthesized with crystallization time varied from 12 to 72 h, characterized by X-ray Diffraction (XRD), textural analysis, Scanning Electron Microscope (SEM), Energy Dispersive X-ray (EDX), and evaluated for the HTL of sugarcane bagasse. All the Fe-MCM-41 catalysts gave higher bio-oil yield with lower oxygen content compared to non-catalytic HTL, confirmed their deoxygenation activity. Among them, Fe-MCM-41 synthesized after 24 h of crystallization was found to have the highest crystallinity, and surface area thus gave the highest bio-oil yield of 56.2% containing the least amount of oxygen of 15.3 wt% at 250 °C, initial CO pressure of 45 bar, reaction time of 120 min, Water/Biomass weight ratio of 28, Catalyst/Biomass weight ratio of 0.4 and 0.2, respectively. Overall process of HTL of sugarcane bagasse was found to involve two consecutive equilibria, first conversion of lignocellulose of sugarcane bagasse by hydrolysis to water soluble organics (WSO) followed by its deoxygenation to bio-oil. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).